Californium versus cobalt brachytherapy combined with external-beam radiotherapy for IIB stage cervical cancer: long-term experience of a single institute - Janulionis, Ernestas; Valuckas, Konstantinas Povilas; Liukpetryte, Sarune; Samerdokiene, Vitalija; Atkocius, Vydmantas (Journal of Contemporary Brachytherapy, 2015)
Purpose: The purpose of this paper was to observe and compare long-term curative effects and complications of FIGO stage IIB cervical cancer patients (n = 232) treated with high-dose-rate (HDR) californium ( 252 Cf) neutron or cobalt ( 60 Co) photon intracavitary brachytherapy (ICBT) combined with external-beam radiotherapy (EBRT). Material and methods: The EBRT dose to the small pelvis was 50 Gy in both groups. The brachytherapy component of 252 Cf or 60 Co was added in the 3 rd week of EBRT, 5 fractions were performed once per week resulting in a total ICBT dose of 40 Gy/Gy eq (point A). Results: Overall survival (OS) at 5, 10 and 15 years was 63.6%, 50.4% and 38.8% in the 252 Cf group and 62.2%, 50.5%, 39.9%, in the 60 Co group, respectively (p = 0.74). The percentage of tumour recurrence was statistically significantly lower in the 252 Cf group with 7.4 % versus 17.1% in the 60 Co group (p = 0.02). Second primary cancers have developed similarly 9.1% and 8.1% cases for 252 Cf and 60 Co groups, respectively. Conclusions : Our long-term retrospective study comparing 252 Cf and 60 Co isotopes with brachytherapy in combined treatment of FIGO IIB stage cervix carcinoma patients shows, that overall survival in the both groups are similar. However, the recurrence of tumour was significantly lower in the